Adipose tissue LECT2 expression is associated with obesity and insulin resistance in Korean women. Issue 7 (20th June 2022) - Kim, Jimin; Lee, Seul Ki; Kim, Donguk; Lee, Eunyoung; Park, Chan Yoon; Choe, Han; Kang, Min‐Ji; Kim, Hwa Jung; Kim, Jong‐Hyeok; Hong, Joon Pio; Lee, Yeon Ji; Park, Hye Soon; et al.
Abstract: Objective: Leukocyte cell‐derived chemotaxin 2 (LECT2) is an obesity‐upregulated hepatokine inducing skeletal muscle insulin resistance. The study's aim was to explore whether LECT2 is expressed in human adipose tissue and whether the expression is dysregulated during obesity and associated with obesity‐related metabolic disorders. Methods: This study measured metabolic parameters, serum LECT2, and expression of LECT2 and CD209, a gene encoding a putative receptor for LECT2, in abdominal subcutaneous and visceral adipose tissues in women with obesity (with or without type 2 diabetes) and women with normal weight. The expression/secretion of LECT2 and its putative effects were assessed in human adipocytes. Results: Adipose tissue LECT2 mRNA and serum LECT2 were higher in women with obesity and were significantly correlated with parameters related to insulin resistance. LECT2 was mainly expressed by adipocytes. Both LECT2 and CD209 expression was higher in adipocytes from women with obesity. Incubating adipocytes with substances mimicking the microenvironment of obesity adipose tissue increased LECT2 expression/secretion. LECT2 treatment of adipocytes suppressed insulin‐stimulated Akt phosphorylation; it reduced adiponectin ( ADIPOQ) and increased leptin ( LEP) expression in a CD209‐dependent manner. Conclusions: This study demonstrates that LECT2 expression in adipose tissue is high in patients with obesity and associated with insulin resistance and suggests that adipocyte‐derived LECT2 may contribute to adipose tissue dysfunction.